225. Evaluating Appropriateness of Antibiotic Prescribing in Pediatric Inpatients - Ray, Michael J (Open Forum Infect Dis, 2020)
BACKGROUND: Antibiotic appropriateness is the gold standard for informing antimicrobial stewardship efforts to optimize prescribing. The objectives of this study were to evaluate appropriateness of antibiotics for resistant gram-positive infections in pediatric inpatients and identify factors associated with inappropriate prescribing. METHODS: We included pediatric inpatients between July 2017 and July 2018 where an antibiotic typically used for resistant Gram-positive infections (per NHSN) was administered. We developed an algorithm based on laboratory data and diagnosis codes to categorize each antibiotic day of therapy as appropriate, inappropriate, or indeterminate. If indeterminate, we reviewed charts to assess appropriateness. We calculated total, appropriate, and inappropriate days of therapy (DOT) overall and per patient-day. We evaluated clinical characteristics and indications as potential predictors of inappropriate DOT using Chi-squared or Kruskal-Wallis tests. RESULTS: Among 591 included encounters, we assessed 708 total antibiotic courses. The algorithm allowed for classification of 422 encounters (71%) and the remaining 171 encounters (29%) were classified using manual record review. The most frequent antibiotics were vancomycin (68%) and clindamycin (29%). Patients received a median of 3 days of gram-positive agent therapy per visit, or 5 per every 10 patient-days. Most common indications for gram-positive therapy were surgical prophylaxis (28% of encounters) and empiric therapy (10%) (Figure 1). Of the 1,754 total days of therapy assessed, 94.8% were ruled appropriate. Thirty-one (4.4%) courses were classified as at least partially inappropriate among 27 unique encounters (4.6%). There was a median of 2 inappropriate days among those with any inappropriate therapy. The reason for inappropriate rulings for empiric or prophylaxis indications was most often “longer than necessary duration,” which was the case for 16 of 21 (76%) occurrences. Figure 1. Appropriate and Inappropriate Days of Therapy (DOT) by Indication and Antibiotic [Image: see text] CONCLUSION: Inappropriate antibiotic use for Gram-positive infections was low in our patient population for the agents studied. We identified limiting the duration for patients receiving prophylactic or empiric therapy as a potential stewardship intervention target. DISCLOSURES: All Authors: No reported disclosures